COUNTERING HIP-HOP AS A BLACK SPACE: HOW “THE OTHERS” STRUGGLED TO FIND SPACE IN RAP BATTLE CULTURE AS ANALYZED IN 8 MILE (2002) AND BAD RAP (2016) - Puteri, Aisha Maura (Rubikon : Journal of Transnational American Studies, 2023)
This article analyzes the normativity of the black race in rap music and how it affected Asian American and White American MCs in Rap Battle (specifically Jin the MC, Dumbfoundead, and Eminem), the importance of rap battle in connection between race and rap, and how rap battle’s connection with race and rap contributed to Jin the MC, Dumbfoundead, and Eminem’s success factors as they tackled racist attacks from their rap battle opponents. The corpus of the study is a documentary about Asian American’s struggle in the hip-hop industry called Bad Rap (2016), as well as Eminem’s revised-autobiography film 8 Mile (2002). The study uses De La Garza and Ono’s CRT (2016) tenets and Edgar and Sedwick’s New Criticism (1999) to discover the importance of Rap Battle in the connection between race and rap as well as the ways that black-originated music affected the nonblack MCs mentioned; specifically, in their performance characteristics, strategies to battle racist attacks from the opponents, as well as their recognition and career development in the industry. Following that, the researcher discussed a gap within racial and sociocultural aspects of black normativity in rap and how it contributed to the ‘success factors’ of these mentioned artists, while racist attacks played a strong role from Black American opponents.